Correspondence of structural components, criteria and measures development of the legal competence of specialists of medical industry in postgraduate education. - Kharkivskyi, V. S. (Problems of Engineer-Pedagogical Education, 2018)
In the article the author defined criteria (reflexive motivational, cognitive activity, communicative-preventive), measures and level (creative (stronger), active (high), regulatory (middle) development of legal competence of specialists of medical industry in postgraduate education. It is shown schematically compliance with the structural components of the criteria and measures of the development of the legal competence of specialists of medical industry in postgraduate education. For evaluation of the level of development of legal competence of specialists of medical industry in postgraduate education, the author offered to use qualimetric diagnostic, qualimetric application-tester, tests. The analysis of scientific and methodological, pedagogical and literature qualimetric model of estimation of the development of the legal competence of specialists of medical industry in postgraduate education is developed.Further scientific research is the author sees in clarifying the current state of development of legal competence of specialists in the field of medical postgraduate education